Reflections on 15 years in the global tobacco trenches - Kenneth D. Ward (New Prairie Press, 2017)
This paper is based on my 2017 Research Laureate Presentation at the annual scientific meeting of the American Academy of Health Behavior in Tucson, Arizona. It provides a brief overview of the history of the smoking epidemic, and describes my work in global tobacco control, focusing on my experiences over the last 15 years as a co-founder and intervention director of the Syrian Center for Tobacco Studies (SCTS) in Aleppo, Syria. The SCTS is an NIH-funded research center that draws on a broad range of complementary expertise and resources from developed and developing nations to address the tobacco epidemic in the Arab World. The SCTS strives to serve as a model of scientific excellence and commitment to the health of people in the Middle East and beyond. Major research streams using qualitative, epidemiological, clinical lab, and intervention methodologies are reviewed, along with some of the successes and challenges encountered since the SCTS's founding.